Analisis Faktor-faktor yang Mempengaruhi Pengungkapan Tanggung Jawab Sosial Perusahaan Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Hendi Hendi; Budi Harsono; Sumantri Sumantri; Silvia Sodia (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to analyze and determine the factors that influence the disclosure of corporate social responsibility. The independent variables in this study are public share ownership, managerial share ownership, foreign share ownership, size of the board of directors, size of audit committee and size of the female board of directors. The control variables in this study are firm size, firm age, leverage and profitability. The dependent variable in this study is the disclosure of corporate social responsibility with the GRI-G4 proxy. The population in this study are all companies that disclose corporate social responsibility listed on the Indonesia Stock Exchange (IDX) through the Indonesia Stock Exchange website (www.idx.co.id) in 2016-2020. Sampling using purposive sampling method as many as 497 companies. Data analysis began with descriptive statistical tests, then continued with panel regression analysis and hypotheses through the E-Views application. The result of this study indicate that public share ownership, managerial share ownership, audit committee size, the size of the female board of directors, firm size and firm age have a significant positive effect on disclosure of corporate social responsibility, profitability has a significant negative effect on disclosure of corporate social responsibility, while foreign share ownership, board of directors size and leverage have no effect on the disclosure of corporate social responsibility.